Communication Analysis of Rubber Farmers in Riau Province, Indonesia - Roza Yulida; Rosnita; Yulia Andriani; Muhammad Ikhwan (International Journal of Media and Communication Research, 2021)
Communication is an essential part of the process of development. Therefore, effective communication is needed to achieve development goals. Rubber is the second largest commodity in Riau Province, after oil palm, and most of rubber commodities are managed by independent rubber farmers. Successful development of rubber farming is needed in order to increase the income and welfare of rubber farmers. However, effective communication is needed to achieve these objectives. The objectives of this study are to; (1) describe the internal and external characteristics of rubber farmers; (2) analyze the relationship between the characteristics and the effectiveness of the communication by rubber farmers. Research was conducted in two potential rubber commodity districts in Riau Province, e.g Kuantan Singingi Regency and Kampar Regency. Respondents in this study were determined by objective sampling and random sampling methods, with 143 rubber farmers as respondents. The results showed (1) the internal characteristics and external characteristics of the rubber farmers in an adequately supportive category; (2) the internal characteristics (education, number of dependents, land area and cosmopolitan area) and the external characteristics (intensity of enhancement, accuracy of extension channels and number of sources of information) have a significant correlation with the efficacy are significant correlated with the effectiveness of group and interpersonal communication. In order for effective communication in farmer group institutions (group communication), it is necessary to increase the intensity of extension, appropriate media extension and increase the number of information sources that are easily accessible by rubber farmers.